Evaluation of the impact of excess sulphide on manganese metal quality - Phahle, Magaboke Themba (My University, 2022)
This work evaluates the challenges of unacceptable high levels of sulphur in the deposited manganese and production losses through uncontrollable cracking at a South African Electrolytic-Manganese (El-Mn) producing company called Manganese Metal Company (MMC). In order to have insight on the high levels of sulphur and the cracking, it was important to first understand the role and effects of sulphide on the manganese metal. Several experiments were conducted in laboratory scale electrowinning cells using the manganese sulphate solution prepared at the MMC plant. The experiments involved varying concentrations of sodium sulphide reagent and aerating the solution to determine the effect. The factorial design tool was used to structure and determine the number of experiments required. The experimental data were collected using equipment such as X-ray fluorescence (XRF), eH/pH probe, LECO CS744 sulphur analyser, Bruker energy dispersive spectrometry (EDS), Scanning electron microscope (SEM) image and airflow meter. Other analytical methods such as titration and qualitative lead acetate test were also adopted to collect the data in the experimental phase. The results were presented in the form of graphs (i.e. line, bar, boxplot and scatterplot), visual pictures, tables and SEM-EDS images. The results show that when sulphide exists in excess in the standard feed solution of an electroplating process, a manganese sulphide (MnS) film was formed on the surface of the metal deposit. The flaking of the metal deposit occurred instantaneously when the solution consisting of excess sulphide was aerated, resulting in a low current efficiency (% C.E) at 13%. The results also indicated that the MnS film was observed at a high level on both run 15 and run 16, where the sulphur (denoted as inherent or intergranular) was measured at 19.2 % and 22.0 % respectively. The low % C.E and increased sulphur was ascribed to the increased presence of thiosulphate and sulphide in the feed solution. It was also confirmed that for every 1 mmol of NaHS concentration consumed, about 0.0095 mmol of thiosulphate is produced. Using a statically based analysis called two-sample t-test, it was indicated that the oxidation of the solution at MMC was significant at the steep transfer launder. This work has shown that when sulphide is present at increased concentrations in the feed solution of a manganese metal electrolytic process, the quality of metal and current efficiency will be drastically reduced.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Science in Engineering to the Faculty of Engineering and Built Environment, University of Witwatersrand, Johannesburg, 2021